The baked side: Cow's milk and egg protein threshold dose distributions in children reacting to baked milk and baked egg - Rocco Luigi Valluzzi, MD; Carla Riccardi, MD; Sara Urbani, MD; Davide Ursi, MD; Deborah Zavettieri, MD; Francesco Di Girolamo, PhD; Lamia Dahdah, MD; Veronica Calandrelli, PharmD; Vincenzo Fierro, MD; Alessandro Fiocchi, MD (World Allergy Organization Journal)
Background: Children allergic to milk and egg, but tolerant to baked products, display higher reactivity thresholds than the general population of children allergic to milk and egg. We sought to verify the reactivity thresholds of milk- and egg-allergic children who also react to baked milk and baked egg, respectively. Methods: We retrospectively assessed consecutive oral food challenge (OFC) for baked milk and egg between January 2018 and March 2022 in a population of baked milk- and baked-egg allergic children. Results: Among 407 children included (median age 56 - IQR 31.1–103.7 months, 67.1% male), 93 (23.6%) returned positive OFC results, 41 with baked milk, and 52 with baked egg. The most conservative ED01 was 0.4 mg total protein (IQR 0.1–2.7) for milk and 2.2 mg total protein (IQR 0.6–7.3) for egg. The respective ED05 was 3.9 (IQR 1.1–14) mg for milk and 11.7 (IQR 5–27.2) mg for egg. Such thresholds are consistent to those found for fresh milk (0.8 times for ED01, 1.1 times for ED05). For egg, they are 6.5 (egg ED01), and 7.5 (egg ED05) times lower than for native form.Compared to the currently used thresholds, they are 1.3 (milk ED01), 1.3 (milk ED05), 11 (egg ED01), and 4.9 (egg ED05) times higher. Conclusions: Milk thresholds are similar to those already observed in baked allergic versus baked tolerant children, while EDs for egg are at least 1.6 times higher than those currently indicated.Egg-allergic patients could be exempt from the recommendations of absolute avoidance of foods when present in infinitesimal quantities, represented by precautionary allergen labelling based on current EDs.